John Ma, Polis. A New History of the Ancient Greek City-State from the Early Iron Age to the End of Antiquity. - Loy, Michael (Journal of Greek Archaeology, 2025)
John Ma’s new magnum opus is over a decade in the making. Originally delivered as the Stanford University 2011 Eitner Lecture on the Greek city-state (pg xv), Ma’s Polis is a tour de force that seeks to undertake a penetrating new analysis of the eponymous ancient political community. Assembling an encyclopaedic quantity of evidence for ancient poleis dating between the Early Iron Age and the End of Antiquity, and weaving a new narrative about the rise and success of early Greek institutional mechanisms, Ma aims to radically shift our understanding of how, when and where the ancient polis was so defined.